Search Behavior and Opinions of Undergraduate Student Users of a Library Discovery System - Shih-Chuan Chen(陳世娟) (Tūzī yǔ dàng’àn xuékān, 2024)
Catalog is an important tool for patrons to inquire and utilize library resources, but search engines have become the main channel for many people to find information or resources. Discovery services help users to search the library resources, institutional repositories, open access content and the subscribed external resources at the same time within a single search box. This study evaluated the performance of undergraduate students when using a discovery system and analyzed the common problems they encountered. Participants' opinions and suggestions regarding the discovery system were also investigated. This study enrolled 16 undergraduate students. Their search behaviors on the discovery system were evaluated using five tasks (three known-item searches and two subject searches), which the participants completed on a laptop. Participants' search processes were video recorded. Follow-up interviews were conducted to solicit the participants' opinions regarding the discovery system. Although the participants had no prior experience with the discovery system, the results revealed high completion rates in most search tasks. Participants described the discovery system as user-friendly and its refinement functions as helpful, and they expressed an intent to use the system in the future. Participants generally employed the single search box and facets during most search tasks, but they used various approaches. The main problems encountered by students were confusion regarding combined search results and ambiguous facet labels. Therefore, the library should improve the design of the interface and provide instructions and guidance on the use of the library Discovery services to attract more students to use it. These findings may help university libraries and vendors better understand undergraduate students' search behavior and the problems encountered by students when using the discovery system.